Flavonoids and Alkaloids from Marine‐Derived Actinomycete Streptomyces sp. C011. Issue 5 (22nd October 2020) - Hoa, Tran Thi Thanh; Van Nam, Vu; Huong, Doan Thi Mai; Dao, Phi Thi; Phuong, Nguyen Nam; Minh, Le Thi Hong; Quyen, Vu Thi; Anh, Nguyen Mai; Murphy, Brian T.; Ly, Ho Thi Minh; Van Cuong, Pham
Abstract: Five secondary metabolites including three flavonoids, 6‐lavandulyl‐5, 7, 2′, 4′‐tetrahydroxyflavanone (1 ), 5′‐lavandulyl‐2′‐methoxy‐2, 4, 4′, 6′‐tetrahydroxychalcone (2 ), 6‐lavandulyl‐7‐methoxy‐5, 2′, 4′‐trihydroxyflavanone (3 ), and two alkaloids, tryptoline (4 ), and norharman (5 ) were isolated from the culture broth of Streptomyces sp. C011. Their structures were determined by spectral data analysis, including MS, 2D NMR, and CD spectrum. All the separated compounds were evaluated for their antimicrobial activities. Compounds 1, 2, 3 and 5 exhibited antimicrobial activity.